Physical activity and the aging brain effects of exercise on neurological function - Watson, Ronald R. (Ronald Ross) (Academic Press, an imprint of Elsevier, 2017)
A complete guide to the manifold effects of exercise and physical activity on the aging brain. This book examines the role that exercise and physical activity play in halting or modulating the deleterious effects of these numerous aging concerns.